Some notes on the computational complexity of optimal aggregation - Peter Winker (Universität Konstanz, Sonderforschungsbereich 178 - Internationalisierung der Wirtschaft, 1992)
A combinatorical problem is said to be of high computational complexity, if it can be shown that every efficient algorithm needs a high amount of resources as measured in Computing time or storage capacity. This paper will (1) introduce some basic concepts of mathematical complexity theory; (2) show that the problem of Optimal Aggregation is of high computational complexity; and (3) outline a possible way to obtain results good enough for practical use despite of this high computational complexity.
Keywords: 330; Aggregation; Mathematische Optimierung; Theorie